Pemeriksaan Sengketa Khusus Pengadaan Tanah untuk Kepentingan Umum - Tiana Afiani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Land acquisition for public interest often gives rise to various legal issues, including disputes between the government, landowners, and other interested parties. These disputes typically revolve around compensation, the acquisition process, and legal certainty. This article aims to analyze the examination mechanism for specific disputes arising from land acquisition for public purposes, by reviewing relevant laws and regulations. The research employs a normative juridical approach to examine statutes, regulations, and court decisions related to land dispute resolution. The findings indicate that although regulations governing dispute resolution mechanisms exist, their implementation often faces challenges, such as unclear compensation values and lack of transparency in the land acquisition process. Therefore, regulatory reforms and increased oversight are necessary to ensure justice and legal certainty for all involved parties.